Paclitaxel-Coated Versus Sirolimus-Coated Eluting Balloons for Percutaneous Coronary Interventions: Pharmacodynamic Properties, Clinical Evidence, and Future Perspectives - Filippo Luca Gurgoglione; Mattia De Gregorio; Giorgio Benatti; Davide Donelli; Luigi Vignali; Emilia Solinas; Iacopo Tadonio; Andrea Denegri; Marco Covani; Gabriella Dallaglio; Bernardo Cortese; Giampaolo Niccoli (Future Pharmacology)
Drug-coated balloons (DCBs) have emerged as an increasingly valuable option for the treatment of coronary artery disease (CAD). Percutaneous coronary intervention (PCI) with DCBs enables the localized delivery of antiproliferative drugs directly to the target coronary lesion, avoiding the need for permanent scaffold implantation. Historically, paclitaxel-coated balloons (PCBs) have been the most used device in this context. Paclitaxel interferes with intracellular microtubule function, leading to cell cycle arrest. However, its cytotoxicity at a higher dosage and narrow therapeutic range has raised some safety concerns. To address these issues, sirolimus-coated balloons (SCBs) have been introduced as an alternative. Sirolimus acts as a cytostatic agent with potent anti-inflammatory and antiproliferative properties and is characterized by a wider therapeutic range, potentially offering a safer profile. Several experimental and clinical studies comparing the safety and efficacy of PCBs versus SCBs have yielded mixed results. Recently, a novel DCB (SirPlux Duo), which simultaneously releases both paclitaxel and sirolimus, has been tested in a porcine coronary model with promising results. In this review, we will elucidate the mechanisms of action of paclitaxel and sirolimus, examine contemporary preclinical and clinical evidence comparing PCB and SCB angioplasty, and discuss novel devices that may enhance the safety and efficacy of PCI with DCBs.